2019
DOI: 10.3390/nu11112674
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness, Sugar-Sweetened Beverages and Fruits Intake in a Rural Population Sample: Data from the Brisighella Heart Study

Abstract: Introduction: There is conflicting information linking fruit and fructose intake with cardiometabolic disorders. The main objective of our study was to evaluate the association between intake of fruits and sugar-sweetened beverages, and carotid-femoral pulse wave velocity (cfPWV), a non-invasive marker of arterial aging, in a large population sample. Methods: For this study, we selected four age and sex-matched subgroups from the last Brisighella Heart Study population survey, after exclusion of those in secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…Several potential mechanisms may describe how SSB consumption could results in increasing the risk of hypertension. Hyperuricemia which is induced by a higher fructose load from sugar-sweetened beverages may leads to acute endothelial dysfunction and chronic Na retention and consequently predisposes individuals to hypertension [ 60 , 61 ]. In this regard, findings from a human study showed a significant increase in blood pressure after acute administration of fructose while this effect was not seen with glucose [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several potential mechanisms may describe how SSB consumption could results in increasing the risk of hypertension. Hyperuricemia which is induced by a higher fructose load from sugar-sweetened beverages may leads to acute endothelial dysfunction and chronic Na retention and consequently predisposes individuals to hypertension [ 60 , 61 ]. In this regard, findings from a human study showed a significant increase in blood pressure after acute administration of fructose while this effect was not seen with glucose [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…For every subject, we recorded a detailed personal history (mainly focused on lifestyle and dietary habits, smoking status and pharmacological treatments), anthropometric data, resting blood pressure and heart rate, the results of standard hematochemistry and of a 12-lead electrocardiogram (Minnesota-coded) [ 16 ]. In particular, over time, the BHS cohort dietary habits has been regularly assessed by the use of the Dietary Quality Index (DQI), a validated tool providing information on the usual food intake of 18 food items, grouped in three food categories [ 17 ]. Based on the questionnaire results, an estimation of the energy intake has also been calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The survey enrolled individuals from BHS who belong to a culturally and dietary homogeneous community that may not be fully representative of the general population. In fact, the mean intake of proteins and animal saturated fats is quite elevated in this area due to the local food culture, despite some educational intervention on the general population [ 26 , 27 ]. Then, the sample size of the high-risk subgroup is relatively small, though representative of the full cohort, and consequently did not allow sub-analyses by age classes or other subgroups.…”
Section: Discussionmentioning
confidence: 99%